2023
DOI: 10.1021/acsomega.2c06408
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dust Layers in Connecting Pipes on Explosion Propagation Characteristics of Flake Aluminum Powder in Cylindrical Interconnected Vessels

Abstract: Aluminum dust explosion has become an important type of dust explosion accident. In the present work, an interconnected system is established to study the influence of accumulated dust layers in connecting pipes on explosion propagation characteristics. A high-precision computational fluid dynamics (CFD) method is applied to study the overpressure and flame development of aluminum powder explosion under the central ignition condition of two cylindrical vessels with a volume ratio of 1:5. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Wang et al 19 conducted a test of coal dust explosion induced by gas explosion in large roadway, and Yu et al 20 conducted an experimental study of coal dust explosion induced by gas explosion, and analyzed that the explosion pressure increased first and then decreased with the increase of coal dust mass, and decreased with the increase of coal dust particle size. Wang et al 21 found that deposition of aluminum powder can significantly increase flame propagation speed and explosion overpressure. Hou et al 22 found that when sedimentary coal dust with different metamorphic degrees participated in the explosion, the peak overpressure and flame propagation speed of composite explosion were positively correlated with the volatile content of coal dust.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 19 conducted a test of coal dust explosion induced by gas explosion in large roadway, and Yu et al 20 conducted an experimental study of coal dust explosion induced by gas explosion, and analyzed that the explosion pressure increased first and then decreased with the increase of coal dust mass, and decreased with the increase of coal dust particle size. Wang et al 21 found that deposition of aluminum powder can significantly increase flame propagation speed and explosion overpressure. Hou et al 22 found that when sedimentary coal dust with different metamorphic degrees participated in the explosion, the peak overpressure and flame propagation speed of composite explosion were positively correlated with the volatile content of coal dust.…”
Section: Introductionmentioning
confidence: 99%